Thiocyanation of Pyrazoles Using KSCN/K2S2O8 Combination - Songsichan, T.; Katrun, P.; Khaikate, O.; Soorukram, D.; Pohmakotr, M.; Reutrakul, V.; Kuhakarn, C. (SynOpen, 2018)
A convenient and practical thiocyanation of pyrazoles is reported employing a combination of KSCN and K2S2O8 in dimethyl sulfoxide (DMSO). The salient features of the present reaction include environmentally benign reagents and solvents, and simple operation. The reaction shows wide functional group tolerance and gives moderate to excellent yields.
Keywords: thiocyanation; pyrazoles; potassium thiocyanate; potassium persulfate; heterocycle